Thermal conductivity of high latitude lunar regolith measured by Chandra’s Surface Thermophysical Experiment (ChaSTE) onboard Chandrayaan 3 lander - Nizy Mathew; K. Durga Prasad; Fazil Mohammad; V. Aasik; Dinakar Prasad Vajja; M. Ram Prabhu; M. Satheesh Chandran; K. P. Subhajayan; Kiran John Antony; P. P. Pramod; Chandan Kumar; Dona Mathew; et al. (Scientific Reports, 2025)
Abstract The thermal conductivity of the lunar regolith is an essential parameter in studying the thermal behavior of the Moon and in planning future lunar exploration. The Chandra’s Surface Thermophysical Experiment (ChaSTE) aboard Vikram lander of the Indian Moon mission Chandrayaan 3 made the first in situ measurement of thermal conductivity of lunar regolith at southern high latitude using a thermal probe with ten temperature sensors at uneven intervals within 10 cm and a foil-type heater wound around the probe close to the nose tip. The ChaSTE thermal probe was inserted into the lunar regolith by a controlled motorized penetration in 29 hours. Through the two active heating experiments at a depth of 80 mm, the thermal conductivity of the lunar regolith at the Vikram landing site is estimated to be 0.0115 ± 0.0008 and 0.0124 ± 0.0009  W m $$^{-1}$$  K $$^{-1}$$ , respectively. The average packing density of the lunar regolith derived using the penetration motor current is 1940 ± 10 kg m $$^{-3}$$ . An empirical model incorporating the temperature and the packing density value yielded thermal conductivity consistent with the in situ measurement. The value of the thermal conductivity measured by ChaSTE is also corroborated by a numerical model.